2010
DOI: 10.1038/jp.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis, respiratory distress syndrome and bronchopulmonary dysplasia in extremely low birth weight infants

Abstract: Objective: To determine if histologic chorioamnionitis (HC) in the presence of respiratory distress syndrome (RDS) augments adverse pulmonary outcomes in extremely low birth weight (ELBW) infants. Results:The mean gestational age of the cases was 27±2 weeks, and the mean birth weight was 791 ± 147 g. A total of 88% (161/184) of patients developed bronchopulmonary dysplasia (BPD). HC was observed in 71 of 238 infants (39%). When infants were divided on the basis of the presence or absence of HC and RDS, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
2
29
0
1
Order By: Relevance
“…One important source of heterogeneity may be the substantial variation in the definition of histological CA. While few of the studies mentioned diagnostic criteria for defining histological CA such as Redline's Criteria, College of American Pathologists Guidelines, Salafia staging system, Blanc's criteria, criteria from Amniotic Fluid Infection Nosology Committee, Roger's protocol and Yoon's criteria, most of them used nonspecified diagnostic methods [36,39,47,58,62,67,69]. Placental microbiology was not taken into account in our analysis due to the insufficient number of studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One important source of heterogeneity may be the substantial variation in the definition of histological CA. While few of the studies mentioned diagnostic criteria for defining histological CA such as Redline's Criteria, College of American Pathologists Guidelines, Salafia staging system, Blanc's criteria, criteria from Amniotic Fluid Infection Nosology Committee, Roger's protocol and Yoon's criteria, most of them used nonspecified diagnostic methods [36,39,47,58,62,67,69]. Placental microbiology was not taken into account in our analysis due to the insufficient number of studies.…”
Section: Discussionmentioning
confidence: 99%
“…In 15 out of these 19 studies, there was a significantly higher GA at birth among the non-CA group compared to the CA group [21,27,28,36,41,43,45,56,57,58,60,62,63,64,65]. Only 8 studies showed no difference among the groups in terms of GA [42,43,47,50,52,58,61,66]. On assessment of the methodological quality using the Newcastle-Ottawa scale, there were no studies in the low-quality group (score 0-3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has therefore been postulated that chorioamnionitis in itself is not a risk factor, and it may even have a protective effect against BPD, whereas subsequent prolonged MV or postnatal infection/inflammation may increase the risk for adverse lung development, thereby leading to BPD. In the case of antenatal infection, signs of fetal inflammation, reflecting a more serious inflammatory state in the fetus, are thought to provoke an impaired surfactant response that is a characteristic of ongoing BPD (25,26). Therefore, a priming microorganism or its related signaling during antenatal infection, together with MV soon after birth may induce lung inflammation, alter the architecture of the immature lung, and compromise postnatal lung development.…”
Section: Articlesmentioning
confidence: 99%
“…4 For the association between HCA and neonatal outcomes of preterm infants, some studies have reported that HCA decre ases the frequency of respiratory distress syndrome (RDS) in preterm infants. 6 However, it is still controversial whether HCA increases the risk of BPD or a poor neurodevelopmental outcome. 79 Such reports have classified their study population according to the presence of HCA only; thus, the control group could contain other significant pregnancy disorders, which could affect neonatal outcomes, and do not represent a 'normal' con trol group.…”
Section: Introductionmentioning
confidence: 99%